2019
DOI: 10.1021/acsomega.9b00577
|View full text |Cite
|
Sign up to set email alerts
|

Green Process without Thinning Agents for Preparing Sebacic Acid via Solid-Phase Cleavage

Abstract: A green and environmentally friendly route of no thinning agent was designed to prepare sebacic acid. Sodium ricinoleate was selected as the raw material to carry out solid-phase cleavage in a tubular furnace. The reaction parameters including catalyst, ratio of sodium ricinoleate/KOH, reaction time, reaction temperature, and absolute pressure were optimized to obtain a high yield of sebacic acid. A satisfactory yield (70.2%) of sebacic acid was received in the presence of 1% catalyst (Fe 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Alkaline strength is an important factor in alkali fusion, the previous research has confirmed that stronger alkalinity is beneficial for the formation of sebacic acid (Yu et al, ). Nevertheless, from the perspective of economy, low‐cost NaOH was used for preparing sebacic acid in this study.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Alkaline strength is an important factor in alkali fusion, the previous research has confirmed that stronger alkalinity is beneficial for the formation of sebacic acid (Yu et al, ). Nevertheless, from the perspective of economy, low‐cost NaOH was used for preparing sebacic acid in this study.…”
Section: Resultsmentioning
confidence: 95%
“…At present, although some new methods regarding preparing sebacic acid have been reported, the disadvantages hamper their further application. For microwave‐induce (Azcan and Demirel, ) and solid‐phase cleavage (Yu et al, ), despite obtaining high yield of sebacic acid, cannot be further utilized into industrialization due to limitations of the reactor. In addition, electrolytic adipic acid (Mathieu, ) and microbial fermentation (Liu and Gao, ) also cannot be used for large‐scale industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, sebacic acid emerged as the highest consumed derivative of castor oil. 61 A product can be manufactured via different routes, but not all are commercially feasible. Similarly, there are different methods of production, but the caustic fusion of castor oil is used on an industrial scale for the production of sebacic acid.…”
Section: Sebacic Acidmentioning
confidence: 99%
“…The major companies producing sebacic acid in China having a production capacity of over 40,000 tons per year are Hebei Hengshui Jinghua Chemical Co., Ltd. and Hebei Kaide Biomaterials Co., Ltd. In 2015, sebacic acid emerged as the highest consumed derivative of castor oil 61 …”
Section: Commercially Vital Derivatives Of Castor Oilmentioning
confidence: 99%
“…[14][15][16] In a recent study sebacic acid was produced in a tubular furnace reactor at a temperature of 270 °C using sodium ricinoleate and potassium hydroxide as raw materials and ferric oxide as catalyst. [17] However, research in this area for producing sebacic acid from castor oil is active due to its huge demand in oleochemical and other industries. In this regard, we attempted to synthesize sebacic acid from castor oil by designing a synthetic route with well-known reagents with a view to explore an alternate route for sebacic acid as India is a major producer of castor oil.…”
Section: Introductionmentioning
confidence: 99%